Cell-derived extracellular matrix-coated silk fibroin scaffold for cardiogenesis of brown adipose stem cells through modulation of TGF-β pathway. Issue 4 (24th April 2020) - Liu, Wei; Sun, Yanfeng; Dong, Xiaohui; Yin, Qi; Zhu, Huimin; Li, Siwei; Zhou, Jin; Wang, Changyong
Abstract: The cell-derived extracellular matrix (ECM)-modified scaffolds have advantages of mimic tissue specificity and been thought to better mimic the native cellular microenvironment in vitro . ECM derived from cardiac fibroblasts (CFs) are considered as key elements that provide a natural cell growth microenvironment and change the fate of cardiomyocytes (CMs). Here, a new hybrid scaffold is designed based on silk fibroin (SF) scaffold and CFs-derived ECM. CFs were seeded on the SF scaffold for 10 days culturing and decellularized to produce CFs-derived ECM-coated SF scaffold. The results showed that the cell-derived ECM-modified silk fibroin scaffold material contained collagen, laminin, fibronectin and other ECM components with myocardial-like properties. Further to explore its effects on brown adipose stem cells (BASCs) differentiation into CMs. We found that the CF-derived ECM-coated scaffold also increased the expression of CM-specific proteins (e.g. cardiac troponin T and α-actinin) of BASCs. Notably, the β1-integrin-dependent transforming growth factor-β1 signaling pathway was also involved in the regulation of CF-derived ECM by promoting the differentiation of BASCs into CMs. Overall, these findings provide insights into the bionic manufacturing of engineered cardiac tissues (ECTs) and establish a theoretical basis for the construction of ECTs.